Project-Based Learning dan Collaborative Learning dalam Pembelajaran Bahasa Arab: Kajian Pedagogis - Harmanto Raharjo; Isop Syafei; Ade Nandang; Aulia Rahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines Project-Based Learning (PBL) and Collaborative Learning (CL) in Arabic language learning from a pedagogical perspective, focusing in particular on the conceptual relationship between the two approaches, which have thus far tended to be studied separately. The study employs a qualitative approach in the form of descriptive-analytical library research. Data were drawn from relevant journal articles, books, and prior studies, and were then analyzed through content analysis and thematic analysis. The findings point to three main conclusions. First, PBL positions Arabic as a communicative tool within authentic tasks—such as thematic dialogues, presentations, and text production—so that language skills become functionally integrated. Second, CL strengthens the dimension of social interaction that renders the use of Arabic active through discussion, peer learning, and group work. Third, the integration of the two forms a mutually complementary pedagogical framework: PBL supplies the structure of project-based tasks, whereas CL sustains the interactional process, so that learning becomes more communicative, participatory, and learner-centered while also reinforcing twenty-first-century skills. Nevertheless, its implementation faces challenges in the form of teacher readiness, time constraints, the heterogeneity of learners’ abilities, and the scarcity of a language-rich environment. Because these findings are conceptual in nature, empirical research is needed to test the effectiveness of this integrative model within broader contexts of Arabic language learning.